Β‐adrenergic signaling promotes posteriorization in Xenopus early development. (3rd March 2013) - Mori, Shoko; Moriyama, Yuki; Yoshikawa, Kumiko; Furukawa, Tomoyo; Kuroda, Hiroki
<x xml:space="preserve">Abstract</x> Adrenaline (also known as Epinephrine) is a hormone, which works as major regulator of various biological events such stages of vertebrate, the role of adrenaline for early embryogenesis has been as heart rate, blood vessel and air passage diameters, and metabolic shifts. Although its specific receptors are expressing at the early developmental stage those functions are poorly understood. Here, we show that loss‐of‐functional effects of adrenergic receptor β‐2 (Adrβ2), which was known as the major receptor for adrenaline and highly expressed in embryonic stages, led posterior defects at the tadpole stage of Xenopus embryos, while embryos injected with Adrβ2 mRNA or treated with adrenaline hormone adversely lost anterior structures. This posteriorization effect by adrenaline hormone was dose‐dependently increased but effectively rescued by microinjection of antisense morpholino oligomer for Adrβ2 (Adrβ2‐MO). Combination of adrenaline treatments and microinjection of Adrβ2 mRNA maximized efficiency in its posteriorizing activity. Interestingly, both gain‐ and loss‐of‐functional treatment for β‐adrenergic signaling could not influence anterior neural fate induced by overexpression of Chordin mRNA in presumptive ectodermal region, meaning that it worked via mesoderm. Taken together with these results, we conclude that adrenaline is a novel regulator of anteroposterior axis formation in vertebrates.